Development of A Guided Inquiry-Based Practicum Guide E-Book In Biology Learning - Dimas Ontowiryo, Moch. Alawi; Wijayanti, Erna; Norra, Bunga Ihda (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2024)
Biology learning can take the form of practical activities that require practical instructions as activity guides. Practical instructions formed in the E-book model will provide advantages in terms of practicality and efficiency. The aim of this research is to make students more active in the biology learning process. This type of research is Research and Development (R&D). The development design used is ADDIE. This research data collection used interview and questionnaire methods. The results of the development of the guided inquiry-based interactive practical e-book were validated by media experts 93% (very feasible), material experts 96% (very feasible), and learning methodology experts 95% (very feasible). From the three validators, an average score of 94% can be taken, so that the guided inquiry-based interactive practicum guide E-book can be declared